Pediculate hepatocarcinoma. - Davidenko, Nicolás; Estapé, Gonzalo; Nuchovich, Gustavo; Lombardi, Gerardo Miguel (Cirugía del Uruguay, 1988)
P An excep\ional case o1 pedlcula\e hepa\ocarcinoma occurring in a previous pathological liver (massive steatosis) is presentad.